Impact of community-based natural resource management on household consumption: a case study of Tonle Sap Lake, Cambodia - Rylida Vong (Journal of Fisheries, 2017)
Community-based natural resource management (CBNRM) is implemented in Tonle Sap Lake (TSL), Cambodia after abolishment of commercial fishing lots in 2001 and 2012. One objective of CBNRM implementation is to reduce poverty of the local communities in TSL. This study aimed to examine the impact of CBNRM on household consumption of fishermen in TSL through Propensity Score Matching method by comparing 248 non-CBNRM households and 223 CBNRM households This study reveals that CBNRM had a negative impact on adult equivalent consumption in the community including the fishermen who fished only inside the community boundary and those who fished both inside and outside the community boundary. However, this study also shows a positive impact of CBNRM on adult equivalent consumption of the households who fished only inside the community boundary. The local community needs more rights to exclude the migrant fishermen and rights to enforce the laws. This study also highlights that alternate income sources should also be created that could be created by expanding the market of the existing ecotourism-job, i.e. hyacinth-made handicraft making.